Karakteristik Kepemimpinan Situasional dan Transformasional dalam Pendidikan Islam Sebuah Tinjauan Mendalam - Amru Abdul Wadud; Zulhimma Zulhimma; Nur Azizah Zulkifli (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the characteristics of situational and transformational leadership within the context of Islamic education and to identify their relevance and integration in developing an adaptive and value-based Islamic leadership model. The research employs a qualitative approach using a library research method through critical analysis of academic literature, books, journals, and Islamic documents related to leadership in education. The findings reveal that situational leadership emphasizes flexibility and the leader’s ability to adjust leadership styles according to the followers’ readiness and needs, while transformational leadership focuses on shaping vision, values, and spiritual motivation to achieve shared goals. In the context of Islamic education, the integration of these two models can be realized through the implementation of Islamic principles such as amanah (trustworthiness), adl (justice), syura (consultation), and hikmah (wisdom), derived from the Qur’an and Sunnah. The study concludes that ideal leadership in Islamic education is adaptive to situations, inspirational in values, and transformative in shaping character and Islamic organizational culture. This research contributes theoretically to the development of a contextual and applicable Islamic leadership paradigm suitable for addressing the challenges of 21st-century education